2017
DOI: 10.4070/kcj.2017.0072
|View full text |Cite
|
Sign up to set email alerts
|

The Use Pattern and Clinical Impact of New Antiplatelet Agents Including Prasugrel and Ticagrelor on 30-day Outcomes after Acute Myocardial Infarction in Korea: Korean Health Insurance Review and Assessment Data

Abstract: Background and ObjectivesDespite the favorable efficacy of new antiplatelet agents demonstrated in randomized controlled trials, their clinical implications in Korea are unclear. The purpose of this study was to investigate trends in antiplatelet agent use for acute myocardial infarction (AMI) and their impact on 30-day clinical outcomes.MethodsAMI patients undergoing percutaneous coronary intervention between 2010 and 2015 were assessed using claim data from the Health Insurance Review and Assessment Service.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Additionally, a recent study based on the Health Insurance Review and Assessment Service Korean database showed that the new-generation P2Y12 inhibitors had favorable effects on 30-day mortality in AMI patients undergoing PCI. 7) However, this was a limited study owing to the lack of information in the nationwide database (data on the predictors of acute complications, such as clinical presentation, left ventricular function, angiographic disease extent, and medication, were not available). Collectively, previous studies failed to provide concrete evidence for the beneficial effects of the new-generation P2Y12 inhibitors in East Asian patients.…”
Section: New-generation Antiplatelet Agents In East Asian Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study based on the Health Insurance Review and Assessment Service Korean database showed that the new-generation P2Y12 inhibitors had favorable effects on 30-day mortality in AMI patients undergoing PCI. 7) However, this was a limited study owing to the lack of information in the nationwide database (data on the predictors of acute complications, such as clinical presentation, left ventricular function, angiographic disease extent, and medication, were not available). Collectively, previous studies failed to provide concrete evidence for the beneficial effects of the new-generation P2Y12 inhibitors in East Asian patients.…”
Section: New-generation Antiplatelet Agents In East Asian Patientsmentioning
confidence: 99%
“…For example, data from the Korean Health Insurance Review and Assessment Service indicated that new-generation P2Y12 inhibitors (prasugrel and ticagrelor) were used in only 40% of the acute myocardial infarction (AMI) population, despite the fact that these agents are recommended over clopidogrel for patients with AMI in the current guidelines. 7) …”
Section: Introductionmentioning
confidence: 99%
“…After a 2-year recruitment period, investigators and data safety monitoring board agreed to terminate the study before achieving target recruitment due to the following reasons: 1) slower patient enrollment than expected, 2) recently updated guidelines recommending the preferential use of ticagrelor in AMI patients, 3) evidence to ensure consistently favorable effects in Asian patients with ticagrelor 12 , and 4) overwhelming use of ticagrelor for AMI patients in Korea. 13 Between March 2014 and March 2016, a total of 106 patients who met the study criteria underwent PCI. A detailed explanation of study flow is provided in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Ticagrelor is the most commonly recommended P2Y12 inhibitor in ACS, and very-low-dose rivaroxaban is currently the only proven oral direct thrombin inhibitor in ACS, while CLP is still widely used in patients with ACS in real-world practice, especially in Korea. [14][15][16] Nevertheless, a direct comparison of the antithrombotic efficacy under in vitro SS conditions among these 3 common strategies has not yet been performed. Therefore, we aimed to comprehensively compare the antithrombotic activities of ticagrelor (TICA), very-lowdose rivaroxaban with CLP (RIVA), and CLP using both the GTT and the VerifyNow test.…”
Section: Introductionmentioning
confidence: 99%